Improving Understanding of Application of ISO/IEC 17025 with the Role-Playing and Simulation Methods in Laboratory Management - Tri Esti Purbaningtias; Thorikul Huda (IJCER (International Journal of Chemistry Education Research), 2017)
ABSTRACT: The application of role-playing learning with self-assessment had been done in the course of Laboratory Management. The application of role-playing learning with self-assessment has been done in the course of Laboratory Management. The learning of role-playing used the module scenario that has been developed based on the general requirements for the competence of testing laboratory and calibration laboratory as stipulated in SNI ISO / IEC 17025. The development of role-playing learning was done through three materials, the making of quality documents, internal audit, and management review, in which each student material will perform the role and proven by video. Self-assessment was based on the competency unit in SKKNI Field of Laboratory Testing Services MSL91600A Develop and maintain laboratory documents, MSL933002A Contribute to the achievement of quality objectives, MSL934002A Implement quality system and continuous improvement process, MSL936001A Maintain quality system and continuous improvement process in work environment, and MSL936002A Carry out internal audits of the quality system. The application of role-playing with self-assessment could give an influence to the improvement of student competency achievement in the competency unit. In class A, student's score of student's previous competency points 39.35% rose to 67.75% and class B rose from 46.51% to 68.95%. The application of role-playing in Laboratory Management could improve the learning outcomes, there is an increase in the number of students who get the value of A that is 13.04% rose to 27.42% while the number of students who got Â£ C decreased 7.22% i.e. from 21.74% to 14.52%. In addition, the application of role-playing method could improve the teaching performance of lecturer by students that is 3.43.Keywords: quality document, internal audit, management review, role-playing, self-assessment, ISO/IEC 17205Â Received: 21 June 2017, Revised: 13 August 2017, Accepted: 2 September 2017